Pandemi Covid-19 dan Transformasi Budaya Digital di Indonesia - Bambang Arianto (Titian: Jurnal Ilmu Humaniora, 2021)
This article aims to elaborate on the impact of the Covid-19 pandemic on the transformation of digital culture in Indonesia. Although digital transformation has occurred so far, the Covid-19 pandemic has also strengthened cultural change at the level of Indonesian society, which in turn created digital culture. In this context, digital culture is the result of thinking, creating and creating digital-based human works. However, the emergence of digital culture has had a positive impact, such as the development of a digital economy ecosystem and the strengthening of civic digital communication. While the negative impact can be seen from lifestyle changes due to the high dependence on social media. This research uses a literature study approach in elaborating the research topic. In the end, this study states that the impact of the Covid-19 pandemic has created a cultural shift from conservative to digital culture. Even so, changes in digital culture at the public level must be anticipated through a program to strengthen digital literacy.